Fabrication of newly-arrived students as mathematical learners - Norén, Eva; Svensson Källberg, Petra (NOMAD Nordic Studies in Mathematics Education, 2018)
As a response to recent laws on how to support newly-arrived students’ schooling, new policy texts have been released in Sweden. By analyzing policy texts we show how a particular kind of human, ”the newly-arrived student as a mathematical learner” is fabricated through discursive processes. We show how the policy texts are framed within an including discourse that encourages multiculingualism and views students’ mother tongue and backgrounds as resources. However, simultaneously the newly-arrived student is thought of, in a more excluding discourse, as being in need of rescue and as lacking the most valuable asset, the Swedish language.